2011
DOI: 10.1016/j.neuropsychologia.2011.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Higher intraindividual variability is associated with more forgetting and dedifferentiated memory functions in old age

Abstract: a b s t r a c tIntraindividual trial-to-trial reaction time (RT) variability is commonly found to be higher in clinical populations or life periods that are associated with impaired cognition. In the present study, higher within-person trial-to-trial RT variability in a perceptual speed task is related to more forgetting and dedifferentiation of memory functions in older adults (aged 60-71 years). More specifically, our study showed that individuals in a high-variability group (n = 175) forgot more memory scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 123 publications
(155 reference statements)
1
19
0
Order By: Relevance
“…These results both suggest that older adults who are more variable are more likely to fail to detect a target, whether this is a prospective memory cue or a visual search target. Similarly, the findings are consistent with research identifying relationships in older adults between IIV and errors on other tasks that may relate to everyday functioning (Bunce et al, 2012;Burton et al, 2009;Papenberg et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…These results both suggest that older adults who are more variable are more likely to fail to detect a target, whether this is a prospective memory cue or a visual search target. Similarly, the findings are consistent with research identifying relationships in older adults between IIV and errors on other tasks that may relate to everyday functioning (Bunce et al, 2012;Burton et al, 2009;Papenberg et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…In a recent study, we showed that older adults who fluctuated more from trial to trial in their RTs forgot more information after 1 week (Papenberg et al, 2011). Neurocomputational simulations (Li, Naveh-Benjamin, & Lindenberger, 2005;Li & Sikström, 2002;Li, Lindenberger, & Sikström, 2001) suggest that suboptimal DA modulation results in a lower signal-to-noise ratio and less distinctive neural representations, which then lead to increased intraindividual variability and lower memory performance at the behavioral level.…”
Section: Discussionmentioning
confidence: 94%
“…In older adults, increased variability has been associated with poorer memory performance (MacDonald, Nyberg, Sandblom, Fischer, & Backman, 2008) and forgetting rates over a one-week period (Papenberg et al, 2011). Across old and young however, increased variability was moderately associated with poorer memory in older adults, but in younger adults, the opposite was found (Vandermorris, Murphy, & Troyer, 2013).…”
Section: Does Within-person Variability Predict Errors In Healthy Adumentioning
confidence: 99%